Is Libra_Facebook’s New Currency Can Increase Financial Inclusiveness? - Handayani, Sri; Martini, Antony; Thomson, Eric M. (KnE Social Sciences, 2020)
Facebook has announced a digital currency named Libra that will allow billions of users to make financial transactions across the planet. Libra which has the Libra Blockchain component, the Libra currency, and Libra association. This article has question on: 1) How could the Libra Association increase financial inclusiveness via its new payment platform? 2) How should Financial and Legal Authorities think of regulating the new Libra virtual currency? Keywords: FinTech, Libra, Financial Inclusion